VALIDITY AND EFFECTIVENESS LESSON PLAN OF PHYSIC LEARNING ARGUMENT DRIVEN INQUIRY (ADI) MODEL ASSISTED BY LECTORA INSPIRE SOFTWARE TO IMPROVE THE SKILLS OF SCIENTIFIC ARGUMENTATION OF HIGH SCHOOL STUDENTS - Hunaidah, Hunaidah (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
Scientific argumentation is an important skill in learning science that is integrated with science learning. The scientific argumentation in the science learning process is the basis for students to think, act and connect knowledge through argumentation to build their knowledge. This study aims to produce a Lesson Plan (LP) on the concept of harmonic motion, sound waves and light with the ADI learning model assisted by Lectora Inspire software that is valid and effective in improving the scientific argumentation skills of high school students. The type of research in this study is Research and Development which adapted the stages developed by Borg & Gall (1989), which are product-oriented in the education field with the research design one-group pretest-posttest design. The trial phase was carried out in Kendari 6 State Senior High School, Kendari 5 State Senior High School and Kendari 9 State Senior High School with 79 research subjects. The results showed that: Lesson Plan with the ADI learning model assisted by the developed Lectora Inspire software had validity with the average Aiken Index V = 0.89 with very high criteria and effectiveness with the Aiken Index VÂ  = 0.77 with high criteria for improving skills scientific argumentation of students.